The waiting period and the distinction between excess and negligence (Journal of the College of Basic Education, 2024)
The research shed light on the provisions of the waiting period and mourning that Sharia has required of women, whether they are in waiting period, such as divorce, death, divorce, curse, and the like, and whether they are Muslim or of the Book, and all the religious, financial, and social provisions that result from that, which women are indispensable for knowing and being aware of. With it, so that they do not fall into the forbidden or prevent themselves from doing what is permissible, or confuse what is permissible and what is not permissible.